Dependence and Guidance Receptors—DCC and Neogenin—In Partial EMT and the Actions of Serine Proteases - Stone, Trevor W. (Frontiers in Oncology, 2020)
The Epithelial-Mesenchymal Transition (EMT) is an important concept in understanding the processes of oncogenesis, especially with respect to the relationship between cell proliferation and metastatic properties such as spontaneous cell motility, chemotaxic migration and tissue invasion. EMT is now recognised as a more complex phenomenon than an all-or-nothing event, in which different components of the EMT may have distinct roles in the physio-pathological regulation of cell function and which may in turn depend on differential interactions with cell constituents and metabolic products. This mini-review summarises recent work on the induction of cancer properties in parallel with the presence of EMT activities in the presence of serine proteases, with the focus on those tumor suppressors known as ‘dependence’ receptors such as neogenin and Deleted in Colorectal Cancer (DCC). It is concluded that various forms of partial EMT should be given more detailed investigation and consideration as the results could have valuable implications for the development of disease-specific and patient-specific therapies.